Lymphoma patients treated with anti-CD20 and chemotherapy display disconnected T and B cell responses to COVID-19 vaccine - Sylvain Lamure; Sylvain Lamure; Houria Hendel Chavez; Marie-Ghislaine de Goër de Herve; Luc-Matthieu Fornecker; Bernard Drenou; Caroline Jacquet; Fatiha Merabet; Milena Kohn; Florence Quélin; Angela Jackson; Sylvain Choquet; et al. (Frontiers in Immunology)
Due to immunosuppressive treatment, COVID-19 vaccination is challenging in patients with B-cell lymphoma. We prospectively evaluated CD4, CD8 T-cell and serological responses to the COVID-19 mRNA vaccine in a cohort of patients treated for a B-cell lymphoma with anti-CD20 therapy. During lymphoma treatment, CD4, CD8, and CD19 cell dropped. While functional-specific CD4 and CD8 T-cell responses to SARS-CoV-2 were unaffected, vaccination in patients on treatment induced low specific antibody titers, contrasting with a preserved serological response when vaccination was completed before treatment initiation. Those findings reinforce a vaccinal strategy based on completion before lymphoma treatment, with a booster administered afterward.